Optimalisasi Program Kesehatan Tradisional melalui Butik Herbal (Bugar dengan Terapeutik Herbal) di UPTD Puskesmas Kenali Besar - Sari, Putri Maya; Nurita, Suci Rahmani (Universitas Baiturrahim, 2025)
The use of Family Medicinal Plants (TOGA) is one of the concerns in the traditional health program at the Kenali Besar Community Health Center (UPTD). Based on a survey in the Kenali Besar Community Health Center (UPTD) area regarding the use of TOGA, it was found that the community's knowledge of medicinal plants is still limited and the use of TOGA is only as ornamental plants and kitchen spices. Therefore, we created the Herbal Boutique Innovation (Fit with Herbal Therapeutics). This community service method is based on coaching, digital literacy-based education, and demonstrations of medicinal plant management in the community/TOGA Independent Care Group in the Kenali Besar Community Health Center (UPTD) area. The effectiveness of the counseling was measured using a pre-test and post-test questionnaire of 10 questions. The purpose of this activity is to increase the understanding of TOGA cadres and the community with a digital and direct information approach. The results of this community service show that a proactive discussion process occurs during the coaching and counseling process. The results of the pre-test and post-test measurements show an increase in the average knowledge score of participants from 58% to 72%. This indicates that the counseling and mentoring activities through the Herbal Boutique Innovation are effective in increasing the cadres' understanding of the use of family medicinal plants. In conclusion, the TOGA Independent Care program, with its Herbal Boutique Innovation, can serve as a platform for enhancing the knowledge of cadres and the community within the Kenali Besar Community Health Center area. It is hoped that this activity can continue with broader coverage